Vocational outcome of intervention for low-back pain - van der Weide, WE; Verbeek, Jos HAM; van Tulder, Maurits W (Scandinavian Journal of Work, Environment & Health, 1997)
Practical management guidelines for occupational health physicians are needed for the individual support of employees with low-back pain. In this study the level of evidence regarding the efficacy of intervention with vocational outcome parameters was assessed. In a systematic literature search, 40 randomized clinical trials on different types of intervention were retrieved. Their internal validity and statistical power criteria were assessed. The randomization procedure, blinding of patients, and sample size were problematic in most studies. For patients with acute low-back pain limited or moderate evidence was found for the efficacy of no bed rest, a short period of bed rest, and spinal manipulation. For chronic patients we found limited evidence for the efficacy of antidepressants or cognitive-behavioral group therapy were effective in comparison with progressive relaxation training. For the other types of intervention, studies with sufficient statistical power were lacking. Such studies are needed before more-detailed evidence-based guidelines can be formulated for occupational health care.
Keywords: absenteeism; evidence-based guideline; guidance; intervention method; sick leave